2018
DOI: 10.7150/thno.27674
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Adipose-Derived Stromal Cells in the Knee of Patients with Severe Osteoarthritis has a Systemic Effect and Promotes an Anti-Inflammatory Phenotype of Circulating Immune Cells

Abstract: Rationale: Recent studies confirmed that osteoarthritis (OA) is associated with systemic inflammation. Adipose-derived stromal cells (ASCs) could become the most promising cell-based therapy in OA, based not only on their differentiation capacities and trophic and paracrine effects on the existing cartilage, but also on their immunomodulatory properties. Here, we wanted to determine the biological effect of autologous ASC intra-articular (IA) injection.Method: To this aim, we monitored the profile of immune ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 50 publications
(46 reference statements)
1
46
0
Order By: Relevance
“…He proposed that the regulation of congenital and acquired immunity may be the mechanism of AMSCs. 84 Russo et al also confirmed that AMSCs are not only a safe therapy, but also found a significant improvement in VAS score, International Knee Documentation Committee (IKDC) score and Tegner-Lysholm (TL) score during oneyear follow-up. 85 Hudetz et al studied the results of the injection of adipose-derived mesenchymal stem cells (AMSCs) from clinic and imaging, respectively.…”
Section: Mesenchymal Stem Cell (Msc)mentioning
confidence: 86%
“…He proposed that the regulation of congenital and acquired immunity may be the mechanism of AMSCs. 84 Russo et al also confirmed that AMSCs are not only a safe therapy, but also found a significant improvement in VAS score, International Knee Documentation Committee (IKDC) score and Tegner-Lysholm (TL) score during oneyear follow-up. 85 Hudetz et al studied the results of the injection of adipose-derived mesenchymal stem cells (AMSCs) from clinic and imaging, respectively.…”
Section: Mesenchymal Stem Cell (Msc)mentioning
confidence: 86%
“…They reported that participants who received low dose of MSCs had the best response in terms of pain and function (Pers et al, 2016). A later study by the same group found that injection of AT-MSCs in the knee triggers a systemic long-lasting immune modulation involving an increase in the percentage of CD4 + CD25 high CD127 low FOXP3 + regulatory T cells and CD24 high CD38 high transitional B cells (Pers et al, 2018b).…”
Section: Clinical Trials Using Mscs For the Treatment Of Knee Oamentioning
confidence: 99%
“…In a clinical trial, Spasovski pointed out that the OA patients treated with single injection of ASCs showed significant cartilage restoration (Spasovski et al, 2018). Similarly, in another trial of OA patients received with ASCs, the ASCs might cause an immediate local response due to released paracrine factors and cytokines for OA amelioration (Pers et al, 2018). Tran et al (2019) employed SVF to regenerate damaged knee cartilage of OA patients, revealing a trend toward a better efficacy of SVF with the microfracture method for OA treatment over a period of two years.…”
Section: Asc-exos In Bone Tissue Damagementioning
confidence: 99%